Comparison of the Effect of Auriculotherapy, a Herbal Compound (Aslagh Capsule), and Metformin on the Clinical Symptoms of Polycystic Ovary Syndrome: Randomized Clinical Trial - Razieh Ghanbarian; Mahboubeh Valiani; Zahra Allameh; Maryam Ranjbar; Mohammad Mazaheri (Advanced Biomedical Research)
Background: Polycystic ovary syndrome (PCOS) is an endocrine disorder that affects women of child-bearing age, with a worldwide prevalence ranging from 6 to 20%. Considering the potential side effects of chemical medications and the need for long-term drug administration, complementary treatments such as acupuncture, auriculotherapy, and herbal medicine have been considered. Hence, this study was designed to compare the effects of auriculotherapy, a herbal component (Aslagh capsule), and metformin on the clinical symptoms of PCOS. Materials and Methods: This is a randomized controlled clinical trial study, which allocated 24 women, aged 18–43 years old, with oligomenorrhea in PCOs, in a 1:1:1 ratio, to three groups. Result: A decreasing pattern in the duration of the menstrual cycle was observed in all three groups, but this was significant only in the auriculotherapy group. There were no significant differences between the three groups in acne and hirsutism scores. However, there was a significant reduction in excess hair growth and density of hair in the auriculotherapy group compared to the other two groups (P < 0.05). Besides, in the auriculotherapy group, the reduction in thickness of excess hair at the end of the second and third months of treatment were marginally significant compared to the two other groups. Conclusions: Auriculotherapy and Aslagh capsule can be effective in reducing PCOS symptoms, similar to metformin. However, auriculotherapy is more effective than the other treatments in reducing the duration of the menstrual cycle, excess hair growth, and hair density.